The Glycosaminoglycan of Recombinant Human Soluble Thrombomodulin Affects Antithrombotic Activity in a Rat Model of Tissue Factor-Induced Disseminated Intravascular Coagulation - Nawa, Katsuhiko; Itani, Teru; Ono, Mayumi; Sakano, Katsu-ichi; Marumoto, Yasumasa; Iwamoto, Masahiro (Thrombosis and Haemostasis, 1992)
Previous studies on recombinant human soluble thrombomodulin (rsTM) from Chinese hamster ovary cells revealed that rsTM was expressed as two proteins that differed functionally in vitro due to the presence (rsTMp) or absence (rsTMa) of chondroitin-4-sulfate. The current study evaluates the in vivo behavior of rsTM in rats and in a rat model of tissue factor-induced disseminated intravascular coagulation (DIC). rsTMp was more potent than rsTMa for prolongation of the activated partial thromboplastin time (APTT) and their in vivo half-lives determined by ELISA were 20 min for rsTMp and 5.0 h for rsTMa. Injection of a tissue factor suspension (5 mg/kg) resulted in DIC as judged by decreased platelet counts and fibrinogen concentrations, prolonged APTT, and increased fibrin and fibrinogen degradation products (FDP) levels. A bolus injection of either rsTM (0.2 mg/kg) 1 min before induction of DIC essentially neutralized effects on platelets, fibrinogen, and FDP levels, and had only a moderate effect on APTT prolongation. The dose of anticoagulant to inhibit the drop in platelet counts by 50% (ED50) was 0.2 mg/kg rsTMa, 0.07 mg/kg rsTMp, and 7 U/ kg heparin. The effect of increasing concentrations of rsTM and heparin on bleeding times were compared in experiments involving incision of the rat tail. Doubling of the bleeding times occurred at 5 mg/kg rsTMa, 3 mg/kg rsTMp or 90 U/kg heparin. These values represent a 25-fold increase over the ED50 for rsTMa, 43-fold for rsTMp and 13-fold for heparin. These results suggest that rsTMp is a potent anticoagulant to inhibit the platelet reduction when injected prior to the induction of DIC in rats.